Between Regulation and Reality: An Analysis of Land Fixed Asset Safeguarding by the Regional Financial and Asset Agency - Salwa Zahara Oktavia; Herjianto Bekti; Mas Halimah (Borong Newinera Publisher, 2026)
Land as a fixed asset of local government carries extraordinary strategic value not merely as material wealth, but equally as an instrument of development and a source of Regional Own Revenue (PAD). Yet in practice, land asset management across many Indonesian regencies and municipalities remains far from ideal. This study examines the safeguarding of land fixed assets implemented by the Regional Financial and Asset Agency (BKAD) of Bandung Regency one of West Java's regions with the highest recorded land asset value. Employing a qualitative descriptive approach through in-depth interviews, field observation, and documentary analysis, the study reveals that the implementation of three asset safeguarding dimensions administrative, physical, and legal as formulated by Suwanda (2013) continues to face serious structural challenges. Of 2,350 registered land parcels, only 483 had been certified as of July 2023, while the full-year certification output for 2022 amounted to a mere 37 parcels. The novelty of this study lies in the identification of three interconnected root causes: inter-agency (SKPD) data disconnection, a deficit in field supervisory human resources, and an accumulation of unresolved historical land ownership problems. Together, these three factors form a vicious cycle that systematically undermines the effectiveness of land asset safeguarding. The study recommends an Integrated Land Asset Security Model (ILASM) built on three pillars: data governance reform, institutional capacity strengthening, and a risk-prioritised land certification acceleration programme.